Financial and Environmental Costs of Reusable and Single-Use Anaesthetic Equipment. Issue 5 (October 2017) - McGain, F.; Story, D.; Lim, T.; McAlister, S.
Abstract : (Abstracted from Br J Anaesth, 118(6):862–869, 2017) Environmental sustainability in anesthesia is gaining importance. Anesthetic equipment for airway management and ventilation can be reusable or single use/disposable, and the comparisons between the environmental effects (carbon dioxide [CO2 ] emissions, water use, etc) of reusables and single-use equipment are more complex and dependent particularly upon the source of energy (eg, coal, renewables) to manufacture or clean the equipment.